2010
DOI: 10.1159/000285165
|View full text |Cite
|
Sign up to set email alerts
|

Association between Renal Function and Clinical Outcome in Patients with Acute Stroke

Abstract: Background and Purpose: Data on the association between renal dysfunction and outcome in patients with stroke are controversial and scarce. We investigated the predictors of renal dysfunction upon admission and the association between renal dysfunction and clinical outcome in patients with acute stroke in a hospitalized Chinese population. Methods: 1,758 acute stroke patients were consecutively enrolled into the study. The estimated glomerular filtration rate (eGFR) was calculated by the Modification of Diet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 40 publications
6
53
1
Order By: Relevance
“…Some studies suggested that reduced eGFR is associated with a poor outcome in ischemic stroke patients (18,19), whereas other studies do not (20,21). Mittleman and colleagues (19) recently demonstrated that a reduced or highly elevated eGFR (,60 or .125 mL/min/1.73 m 2 ) was associated with a higher mortality rate compared with patients with moderate levels of eGFR in 1,175 acute ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that reduced eGFR is associated with a poor outcome in ischemic stroke patients (18,19), whereas other studies do not (20,21). Mittleman and colleagues (19) recently demonstrated that a reduced or highly elevated eGFR (,60 or .125 mL/min/1.73 m 2 ) was associated with a higher mortality rate compared with patients with moderate levels of eGFR in 1,175 acute ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed study design and methods have been previously published. 23 Continuous data are presented as the mean ± standard deviation (SD) or median and interquartile range (IQR) (25th to 75th percentile) in the case of non-normal distributions. Discrete data are given as counts and percentages.…”
Section: Methodsmentioning
confidence: 99%
“…In Hao et al’s (2010) study, the mean e-GFR at admission in the haemorrhagic and ischemic stroke groups were comparable 77.57 ± 51.73 vs 77.07 ± 29.89 (p=0.285) 19 . Patients presented to our centre at various times following the index stoke; hence, the days mentioned are not the days after the stroke event, but the days after admission to the hospital.…”
Section: Discussionmentioning
confidence: 83%